Mutations in GFPT1 that underlie limb-girdle congenital myasthenic syndrome result in reduced cell-surface expression of muscle AChR. - Zoltowska, K; Webster, R; Finlayson, S; Maxwell, S; Cossins, J; Müller, J; Lochmüller, H; Beeson, D (2013)
Mutations in GFPT1 underlie a congenital myasthenic syndrome (CMS) characterized by a limb-girdle pattern of muscle weakness. Glutamine-fructose-6-phosphate transaminase 1 (GFPT1) is a key rate-limiting enzyme in the hexosamine biosynthetic pathway providing building blocks for the glycosylation of proteins and lipids. It is expressed ubiquitously and it is not readily apparent why mutations in this gene should cause a syndrome with symptoms restricted to muscle and, in particular, to the neuromuscular junction. Data from a muscle biopsy obtained from a patient with GFPT1 mutations indicated that there were reduced endplate acetylcholine receptors. We, therefore, further investigated the relationship between identified mutations in GFPT1 and expression of the muscle acetylcholine receptor. Cultured myotubes derived from two patients with GFPT1 mutations showed a significant reduction in cell-surface AChR expression (Pt1 P < 0.0001; Pt2 P = 0.0097). Inhibition of GFPT1 enzymatic activity or siRNA silencing of GFPT1 expression both resulted in reduced AChR cell-surface expression. Western blot and gene-silencing experiments indicate this is due to reduced steady-state levels of AChR α, δ, ε, but not β subunits rather than altered transcription of AChR-subunit RNA. Uridine diphospho-N-acetylglucosamine, a product of the hexosamine synthetic pathway, acts as a substrate at an early stage in the N-linked glycosylation pathway. Similarity between CMS due to GFPT1 mutations and CMS due to DPAGT1 mutations would suggest that reduced endplate AChR due to defective N-linked glycosylation is a primary disease mechanism in this disorder.